Tahlil al-Akhto' al-Imlaiyah fi al-Hamzah Lada Thullab Ma'had al-Lughawiyat al-'Arobiyah Bi Jami'ati al-Malik Sa'ud - Abdelaziz Haroun Abdoulaye (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2020)
This study aimed to know the spelling errors in Hamza among students of the Institute of Arabic Linguistics at King Saud University. The sample of the study consisted of (23) students represented in three levels: (beginner, intermediate and advanced) .The study relied on the descriptive analytical research methodology. To collect information from the study sample, the validity and reliability of the tool was verified by presenting it to a group of arbitrators with competence in the field. The results of the study indicated that there are statistically significant differences between the three levels. (37%), and The percentage of errors in writing Hamza in the middle of the word reached (55%), and the percentage of errors in writing Hamza in the back of the word (08%). As for the percentage of mistakes of middle level students in the writing of extreme Hamza (25.4%), and the percentage of mistakes in writing Hamza in the center of the word (57.3%), and the percentage of errors in the writing of extreme Hamza reached (17.3%).Â As for the advanced level students, the percentage of their mistakes in writing the Hamza at the beginning of the word (33.3%), and the percentage of errors in writing in the middle of the word (60%), and errors related to the writing of the Hamza at the end of the word (06.7%), as a resultÂ The study concluded with a set of recommendations in the light of the results shown.